Structural state of rare earth elements in eudialyte-group minerals. (February 2020) - Borst, Anouk M.; Finch, Adrian A.; Friis, Henrik; Horsburgh, Nicola J.; Gamaletsos, Platon N.; Goettlicher, Joerg; Steininger, Ralph; Geraki, Kalotina
Abstract: Eudialyte-group minerals (EGM) attract global interest as potential resources for high-field-strength elements (e.g. Zr, Nb, Ta, and rare-earth elements), i.e. critical materials for modern technologies. They are particularly valued for their relative enrichment in the most critical lanthanides, i.e. Nd and heavy rare earth elements (Gd–Lu). However, rare earth element ( REE ) substitution mechanisms into the EGM structure are still poorly understood. Light and heavy REE may occupy different sites and there may be ordering and/or defect clustering in the structure. This study uses X-ray absorption spectroscopy to determine the structural state of REE in EGM from prospective eudialyte-bearing complexes. Yttrium K -edge and Nd L 3 -edge spectra were collected as proxies for heavy and light REE, respectively, and compared to natural and synthetic REE -bearing standards. Extended X-ray absorption fine structure data yield best fits for Y in six-fold coordination with Y–O distances of 2.24–2.32 Å, and a second coordination sphere comprising Fe, Na, Ca, Si and O at radial distances of 3.6–3.8 Å. These findings are consistent with dominant Y 3+ substitution for Ca 2+ on the octahedral M 1 site in all the samples studied, and exclude preferential substitution of Y 3+ onto the smaller octahedral Z site or the large low-symmetry N 4 site. Using lattice strain theory, we constructed relative partitioning models to predict site preferences of lanthanides we have not measured directly. The models predict that all REE are favoured on the Ca-dominant M 1 site and that preferential partitioning of heavy over light REE increases in EGM containing significant Mn in the M 1-octahedral rings (oneillite subgroup). Thus, the flat REE profiles that make EGM such attractive exploration targets are not due to preferential partitioning of light and heavy REE onto different sites. Instead, local ordering of Mn- and Ca-occupied M 1 sites may influence the capacity of EGM to accommodate heavy REE .